2020
DOI: 10.3390/en13081877
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis on the Effectiveness of Gurney Flaps as Power Augmentation Devices for Airfoils Subject to a Continuous Variation of the Angle of Attack by Use of Full and Surrogate Models

Abstract: The disclosing of new diffusion frontiers for wind energy, like deep-water offshore applications or installations in urban environments, is putting new focus on Darrieus vertical-axis wind turbines (VAWTs). To partially fill the efficiency gap of these turbines, aerodynamic developments are still needed. This work in particular focuses on the development of a mathematical model that allows predicting the possible performance improvements enabled in a VAWT by application of the Gurney flaps (GFs) as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…According to the technical literature [11,12], it was found that the height of the GF should be kept below the boundary layer thickness in order to obtain a beneficial lift-to-drag ratio. In previous works carried out by some of the authors for VAWTs applications [13,14], it was found that the best performance can be achieved when a GF with a height of 2%c was applied on the inner side of the airfoil.…”
Section: Design Considerations and Scope Of The Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to the technical literature [11,12], it was found that the height of the GF should be kept below the boundary layer thickness in order to obtain a beneficial lift-to-drag ratio. In previous works carried out by some of the authors for VAWTs applications [13,14], it was found that the best performance can be achieved when a GF with a height of 2%c was applied on the inner side of the airfoil.…”
Section: Design Considerations and Scope Of The Activitymentioning
confidence: 99%
“…The numerical investigation was performed by means of two dimensional CFD simulations with the commercial software ANSYS ® FLUENT ® . The computational framework was thoroughly assessed and validated with experimental data for various test cases by some of the authors in previous studies [13][14][15][16][17][18]. According to previous results, the unsteady Reynolds-Averaged Navier-Stokes (URANS) approach was adopted with the Menter's κ-ω SST (shear stress transport) model for turbulence closure.…”
Section: Study Casementioning
confidence: 99%
See 1 more Smart Citation
“…Mostly it is used as a propulsion of small unmanned aerial vehicles in aviation, in maritime its variant in the form of a cycloidal propeller is used for maneuvering the ship [2][3][4][5][6][7][8][9][10]. Thanks to its advantages, such as, the possibility of a quick change of the flow direction [9][10][11], higher flow efficiency than in the case of machines without cycloidal regulation and the possibility of using a Gurney flap (for fans) [12]. It can also be used for HVAC.…”
Section: Introductionmentioning
confidence: 99%
“…Developments are needed in each of them, from more accurate but computationally affordable simulation techniques [11,12], to innovative control logics [13] or effective methods for noise prediction [14]. Focusing more specifically on aerodynamics, it is apparent that the use of high-fidelity computational techniques is key to properly model the new generation of long and flexible blades, where aero-elastically-tailored designs are needed, and different flow control devices are often used to alleviate the loads [15,16]. As discussed, all these new methods and tools, however, should be developed synergically by the different groups of specialists, in view of that integration that represents the only way of properly addressing the reliable modeling of such a complex system like a wind turbine.…”
mentioning
confidence: 99%